Effectiveness of The Audit Program, Integrity and The Government Internal Control System on Prevention of Fraud in The Procurement of Goods and Services - Daning Ayu Ningsih; Helmi Yazid; Dadan Ramdhani (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study is to determine whether the effectiveness of probity audit, integrity, and the government's internal control system (SPIP) affects fraud in the procurement of goods and services in Serang district. This research uses quantitative methods. The sampling technique uses cluster sampling. The population in this study was a whole local government organization with a total of 27 and each OPD was given 5 questionnaires. The analysis method used in this study is the coefficient of determination method. The data processing process uses SmartPLS software version 3. The type of data used in this study is primary data. Path analysis and bootstrapping technique were used to test the hypothesis. The results of this study show that the effectiveness of the audit probity and the government's internal control system had a positive and significant effect on the prevention of fraud in the procurement of goods and services while for integrity it had no effect and was significant on the prevention of fraud in the procurement of goods and services.